The beneficial effect of leaf removal during fruit set on physiological, biochemical, and qualitative indices and volatile organic compound profile of the Cypriot reference cultivar 'Xynisteri' - Georgiadou, Egli C.; Mina, Minas; Neoptolemou, Varnavas; Koundouras, Stefanos; D'Onofrio, Claudio; Bellincontro, Andrea; Mencarelli, Fabio; Fotopoulos, Vasileios; Manganaris, George A. (My University, 2023)
Background:‘Xynisteri’is the reference Cypriot white cultivar that, despite its significant societal and economic impact, ispoorly characterized regarding its qualitative properties, while scarce information exists regarding its aroma profile. In the cur-rent study, the effect of leaf removal during fruit set (BBCH 71) on 6-year cordon-trained, spur-pruned grapevines was assessedand an array of physiological, biochemical, and qualitative indices were monitored during successive developmental stages(BBCH 75, BBCH 85, BBCH 87, and BBCH 89). Grapes were additionally monitored for the volatile organic compounds (VOCs)profile during the advanced on-vine developmental stages (BBCH 85–BBCH 89) with the employment of gaschromatography–mass spectrometry (GC–MS), Fourier-transform near infrared (FT-NIR) spectra and electronic nose (E-nose)techniques.Results: Grape berries from the vines subjected to leaf removal were characterized by higher solid soluble sugars (SSC), titrat-able acidity (TA), tartaric acid, and ammonium nitrogen contents, while this was not the case for assimilable amino nitrogen(primary amino nitrogen). A total of 75 compounds were identified and quantified, including aliphatic alcohols, benzenic com-pounds, phenols, vanillins, monoterpenes, and C13-norisoprenoids. Leaf removal led to enhanced amounts of glycosylatedaroma compounds, mainly monoterpenes, and C13-norisoprenoids. Chemometric analysis, used through FT-NIR and E-nose,showed that the aromatic patterns detected were well associated to the grape ripening trend and differences between leafremoval-treated and control grapes were detectable during fully ripe stage.Conclusion: Leaf removal at fruit set resulted in an overall induction of secondary metabolism, with special reference to glyco-sylated aroma compounds, namely monoterpenes and C13-norisoprenoids
Keywords: C13-nosisoprenoids; E-nose; FT-NIR; GC-MS; Chemometrics; Indigenous cultivar; Monoterpenes; Volatile organic compounds (VOCs); Chemometrics